2008
DOI: 10.1080/13811110802324847
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Interpersonal-Psychological Variables in Air Force Suicides: A Controlled-Comparison Study

Abstract: Joiner's (2005) theory attributes suicide to an individual's acquired capability to enact self-harm, perceived burdensomeness, and thwarted belongingness. This study evaluated whether Joiner's theory could differentiate United States (US) Air Force (AF) personnel (n = 60) who died by suicide from a living active duty AF personnel comparison sample (n = 122). Responses from AF personnel on several scales assessing Joiner's constructs were compared to data from a random sample of postmortem investigatory files o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 20 publications
5
46
1
2
Order By: Relevance
“…This was similar to the percentages reported by Preau and colleagues (2008) in their randomized study on male and female participants conducted in 102 hospital departments in France, Cooperman and Simoni's (2005) study on women only, and Haller and Miles (2003) on a group of psychiatrically hospitalized HIV/AIDS patients. However, the percentage was lower than Nademin et al (2008) found in their study that compared HIV-infected people with non-HIV-infected people. Many statistics report suicidal behaviors are higher in women than in men, yet this was not the case in our sample and we found no difference in the prevalence between the two groups.…”
Section: Discussioncontrasting
confidence: 75%
“…This was similar to the percentages reported by Preau and colleagues (2008) in their randomized study on male and female participants conducted in 102 hospital departments in France, Cooperman and Simoni's (2005) study on women only, and Haller and Miles (2003) on a group of psychiatrically hospitalized HIV/AIDS patients. However, the percentage was lower than Nademin et al (2008) found in their study that compared HIV-infected people with non-HIV-infected people. Many statistics report suicidal behaviors are higher in women than in men, yet this was not the case in our sample and we found no difference in the prevalence between the two groups.…”
Section: Discussioncontrasting
confidence: 75%
“…A psychological autopsy study found that retrospectively assessed levels of acquired capability—sample items included the prior engagement in suicide-preparatory behaviors, past suicide attempts, and problems with impulsivity—discriminated between living controls and those who died by suicide in a military sample (Nademin, Jobes, Pflanz, Jacoby, Ghahramanlou-Holloway, Campise, et al, 2008). …”
Section: Constructs Of the Interpersonal Theory Of Suicidementioning
confidence: 99%
“…A random sampling procedure was used to select 10% of coded cases for evaluating inter-rater reliability. Reliability was high across coded variables with kappa coefficients ranging from 0.6 to 1.0, as previously reported (Nademin et al, 2008). Institutional review board permission was obtained for the study.…”
Section: Data Extractionmentioning
confidence: 74%
“…All of the available files from 2000 to 2006 were coded, resulting in 219 of the 258 (85%) USAF suicides during those seven years. Files from 1996 to 1999 were randomly selected because they were part of a different project that used the same coding form (Nademin et al, 2008). Of the 237 airmen who died by suicide, 98 (41%) left a suicide note.…”
Section: Samplementioning
confidence: 99%